Optimalisasi Pengelolaan Sampah untuk Potensi Ekonomi melalui Workshop Lingkungan di Desa Mandiri Banyurejo - Yutta Vemin Hanafi; Bondan Megantoro; Fransiska Dabi; Chandra Pratama; Fransiskus F.H. Thoba; Petronela Solossa; Moch G. A.A. Ari; Achmad M. Gyiansyah; Norbertus Klau; Rachmadhani R. Herlansyah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
The Community Service Program (KKN) is an intracurricular activity that is mandatory for students as a form of community service. In this context, the KKN group R1 of Janabadra University Yogyakarta conducted a service activity in Banyurejo Village, Yogyakarta City, for six weeks. This activity carried the main theme of community empowerment in environmental management, with a primary focus on increasing awareness of the economic potential of waste through the implementation of an Environmental Workshop with the theme "Waste as Economic Potential: Creating an Independent and Clean Village." This workshop was the core agenda that involved the active participation of residents in discussing and practicing waste management that was wise, economically valuable, and environmentally friendly. To support this main activity, several supporting programs were also implemented, including: Ceria Class as a medium for environmental education for children, the establishment of a Waste Bank, joint exercise activities with residents, village clean-up actions, synergy with the PKK women's group, and educational seminars on the environment and health. All activities were designed with a community-based educational and participatory approach, to encourage direct community involvement in creating change. During the implementation period, this program showed positive results. There was an increase in public awareness of the importance of structured and sustainable waste management. Furthermore, residents have begun to demonstrate their initiative by establishing neighborhood-level waste banks, demonstrating their commitment to community-based waste management. Participation from various community elements, including children, housewives, and community leaders, is key to the success of this initiative. The success of the Janabadra University Community Service Program (KKN) group R1 is expected to serve as a model for other regions in designing and implementing community empowerment programs, particularly in the environmental sector.